A prospective evaluation of the community assessment tools (CATs) in children and adults with acute lower respiratory tract infections: an external validation study - Armon, Ruby (2017)
Background: CATs is a hospital admission triage tool for influenza and pneumonia, and comprises of 7 criteria (6 objective and 1 subjective); any one of which is expected to trigger hospital admission in adults and children. As the CATs was only recently developed, its performance has only been assessed in the United Kingdom using data from the 2009 A (H1N1) flu pandemic. An external validation study is thus required to assess the generalisability of the CATs in a new patient population before it is recommended for adoption in practice.